Mechanical performance test and analysis of prestressed lightweight aggregate concrete hollow slab. Issue 8 (June 2019) - Li, Shiping; Song, Chao
To investigate the mechanical performance of prestressed lightweight aggregate concrete hollow slabs, a symmetric loading test was performed on eight prestressed concrete hollow slabs categorised into four groups based on their variety of coarse aggregate concrete and span, and their respective failure mode, bearing capacity, deformation performance and crack propagation were analysed. Based on the test data, a simulation model was subsequently established to simulate and analyse the test components. The test results showed that the bending process of the prestressed lightweight aggregate concrete hollow slab goes through three stages: elasticity, elasto-plasticity and plasticity. Furthermore, its bearing capacity and failure characteristics are similar to those of a prestressed ordinary concrete hollow slab. Subsequently, we derived a formula for checking the calculation of crack width by introducing a comprehensive influence coefficient of concrete Cm and combining it effectively with the formula in the current code and verified its efficacy. The calculated value of the formula agrees well with the test results, providing a reference for the application of engineering and a supplementary calculation formula for the crack width of lightweight aggregate concrete hollow slabs.